Sputtering of paraboloid microstructure using fib - Ali, Mohammad Yeakub; Loo, Y. W. (2006)
This paper describes the fabrication of three dimensional (3D) microstructures using focused ion beam (FIB) sputtering. Paraboloid cavity was chosen as an example for 3D microstructure. This microstructure was considered as the combination of a series of flat circular slices. The successive slices were 1 μm smaller in diameter compared to the previous layers. The diameters of the biggest and smallest slice were 16 μm and 1 μm respectively. The thickness of each slice was about 0.2 μm. An appropriate amount of ion dose was delivered to sputter the particular thickness for each slice. The slice by slice sputtering command was given by the Micrion DMOD description language (MDDL). Geometry and surface characteristics of microparaboloid structures were investigated by using scanning electron microscope (SEM) and atomic force microscope (AFM). The diameter at the top and depth of the sputtered paraboroid were found to be 16 μm and 3.2 μm respectively.